.

Jordan

De por WikiMatematica.org

Ejemplo

Para el sistema dado:

I/O: \dddot{x}+6\ddot{x}+11\dot{x}+6x=6y(t)\ \ \ //\mathfrak{L}\{\}


P^3X(P)+6P^2X(P)+11PX(P)+6X(P)=6Y(P)


\left [  P^3 +6P^2 +11P +6 \right ] X(P)=6Y(P)


\frac{X(P)}{Y(P)}=\frac{6}{P^3 +6P^2 +11P +6}


G(P)=\frac{6}{P^3 +6P^2 +11P +6}=\frac{6}{P+1}\cdot\frac{1}{P+2}\cdot\frac{1}{P+3}


Fnj.jpg


Encontramos las variables de estado:


q_1(p)=\frac{6}{P+1}\cdot Y(P)


(P+1)q_1(p)=6Y(P)\} \ \ //\mathfrak{L}^{-1}\{\}


\dot{q_1}(t)+q_1(t)=6y(t)


\dot{q_1}(t)=-q_1(t)+6y(t)


q_2(p)=\frac{1}{P+2}\cdot q_1(P)


(P+2)q_2(p)=q_1(P)\} \ \ //\mathfrak{L}^{-1}\{\}


\dot{q_2}(t)+2q_2(t)=q_1(t)


\dot{q_2}(t)=q_1(t)-2q_2(t)


q_3(p)=\frac{1}{P+3}\cdot q_2(P)


(P+3)q_3(p)=q_2(P)\} \ \ //\mathfrak{L}^{-1}\{\}


\dot{q_3}(t)+3q_3(t)=q_2(t)


\dot{q_3}(t)=q_2(t)-3q_3(t)

Ecuaciones Dinámicas:

\dot{q}(t)=\begin{bmatrix} -1 & 0 & 0\\ 1 & -2 & 0\\ 0 & 1 & -3 \end{bmatrix}q(t)+\begin{bmatrix} 6\\ 0\\ 0 \end{bmatrix}y(t)


Ecuación de Lectura:

x(t)=\begin{bmatrix} 0 & 0 & 1 \end{bmatrix}q(t)+0\cdot y(t)

Anuncios